The Effect of Passive Range of Motion on Recovery Time in Post-Operative Patients in the Recovery Room of Brawijaya University Hospital Malang - Mujiadi; Fatmawati, Atikah (Al-Hijrah Indonesia, 2023)
Recovering from general anesthesia is a risk factor for morbidity and mortality in any operation. One of the main complications after anesthesia is delayed recovery. This study aims to determine the effect of passive ROM mobilization on the recovery time of post-operative patients with general. This type of research is quantitative with a research design quasy experienceuse Post-test Only non-equivalent Control Group Design. The population is patients who underwent surgery with general anesthesia, amounting to 40 people. Sampling using consecutive sampling with a total sample of 40 people divided into 2 groups, the control group of 20 people and the experimental group of 20. Measuring tool using observation score Aldred and patient recovery time. The data was analyzed using Paired T-test. The results of the study showed that most of the control group respondents experienced recovery time of >15 minutes (65%) and most of the experimental group respondents experienced <15 minutes of recovery time (70%). The nurse immediately did Range Of Motion Passive after the patient finished surgery with general anesthesia in order to help expel secretions in the respiratory tract, accelerate peripheral circulation to support optimal respiratory function, and improve the body's metabolism and physiology of vital organs that affect recovery.